RETINAL THICKNESS AND RNFL EVALUATION BY OCT IN RADIOLOGY TECHNICIANS EXPOSED TO X-RAYS WITHOUT EYE PROTECTION IN AMAZONIAN CLINICS - Almeida, Leidiana Silva de; Alves, Luana Cristina Lucas; Rissino, Jonathan Miranda; Ferreira, Gustavo Miranda de Azevedo; Rodrigues, Anderson Raiol; Teixeira, Cláudio Eduardo Corrêa (Indonesian Vitreoretinal Society, 2025)
Introduction: While the ocular effects of ionizing radiation have been widely studied, little is known about its impact on the retinas of radiology professionals exposed daily without protective eyewear. This study aimed to assess potential morphological retinal changes using optical coherence tomography (OCT) in radiology technicians working without X-ray protective glasses. Methods: A total of 11 radiology technicians routinely exposed to X-rays without eye protection were compared with 9 age-matched controls not exposed to ionizing radiation. Subjects with systemic conditions affecting the retina (e.g., diabetes, hypertension) were excluded. OCT scans were performed using Heidelberg Spectralis OCT to assess retinal nerve fiber layer (RNFL) thickness and global retinal thickness.Given the small sample sizes, a descriptive comparison approach was used. Results: RNFL thickness was thinner in the exposed group compared to controls, particularly in the superior and nasal quadrants. Three individuals in the exposed group showed global retinal thickness below normal limits, compared to one in the control group. The proportion of subjects with retinal thinning was higher in the exposed group, especially in the macula and RNFL. A qualitative assessment revealed temporal macular thinning and superior RNFL thinning around the optic disc. Conclusion: These findings suggest that chronic X-ray exposure without protective eyewear may be associated with retinal thinning and RNFL loss in radiology technicians. Given the small sample size, further research with larger cohorts is needed to confirm long-term effects and establish preventive measures.